Kreatifitas dan Pendidik PAUD dalam Perspektif Peluang dan Tantangan - Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
Being an educator for early childhood has a different challenge with educators in other age groups, because early childhood have different characteristics. One of the things that educators need to understand is that early childhood children have the ability to concentrate/focus very limited attention. The ability to bring creative learning media can make the learning process for early childhood always attract and provoke a child's curiosity, so that children are able to take longer learning activities. Decoupage creativity is one of the learning media that can be used by educators in stimulating early childhood intelligence. Furthermore decoupage creativity can also be used as a source of income for PAUD educators.Keywords: Creativity, Educators, Opportunities, Challenges